2020
DOI: 10.1029/2019jc015639
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and Thermohaline Variability of the Hanna Shoal Region on the Northeastern Chukchi Sea Shelf

Abstract: We analyzed velocity and hydrographic data from 23 moorings in the northeast Chukchi Sea from 2011 to 2014. In most years the eastern side of Hanna Shoal was strongly stratified year‐round, while weakly stratified regions prevailed on the shelf south and west of the Shoal. Stratification differences cause differential vertical mixing rates, which in conjunction with advection of different bottom water properties resulted in seasonally varying along‐isobath density gradients. In agreement with numerical models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…This is consistent with the results of Fang et al. (2020).…”
Section: Seasonalitysupporting
confidence: 94%
See 2 more Smart Citations
“…This is consistent with the results of Fang et al. (2020).…”
Section: Seasonalitysupporting
confidence: 94%
“…However, three of the mooring records (Cj, CT, and FM1) were short by 1-3 months. We note that some, but not all, of the moorings analyzed in this study are the same as those discussed in Fang et al (2020).…”
Section: Mooring Datamentioning
confidence: 95%
See 1 more Smart Citation
“…Local winds over the Pacific-sector Arctic continental shelves can account for 30−50% of the synoptic scale variability in the coastal region, while including time-lagged remote winds can increase the fraction of variance explained by 10−20% (Danielson et al, 2014;Weingartner et al, 2017;Fang et al, 2020). Using a 1-layer (two-dimensional barotropic) model of the Pacific Arctic forced only by wind, Danielson et al (2014) showed that including the combined effects of locally generated storm surges and their associated propagating shelf waves provides a skilfull reproduction of observed current variations in Bering Strait (r 2 = 0.79 in winter months) for synoptic-band current fluctuations.…”
Section: Linking the Shelvesmentioning
confidence: 99%
“…Circulation patterns showed a general clockwise flow around the north and east sides of Hanna Shoal, as well as on the west flank. Unlike the rest of the shelf, observations east of Hanna Shoal indicated the circulation and hydrography maintained a year-round stratification with westward or northwestward flow in the upper layer and southward flow along the bottom [134].…”
Section: Field Observationsmentioning
confidence: 99%